2007
DOI: 10.1038/sj.clpt.6100274
|View full text |Cite
|
Sign up to set email alerts
|

Professional Students' Perceptions of the Value, Role, and Impact of Science in Clinical Education

Abstract: Health sciences curricula are, by definition, built on a foundation of scientific knowledge and inquiry. Professional programs in fields such as medicine, pharmacy, nursing, physical/occupational therapy, and dentistry purport to provide students with the ability to translate scientific knowledge and understanding into clinical practice, for improving the health and well-being of patients. Indeed, the scientific underpinning of each health profession is a point of pride, a reason these roles exist in the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…19 Clinical courses have introduced innovative pedagogies to motivate students and animate learning while most science courses remain strongly didactic, uninteresting, and of poor quality. 19 Although these challenges may exist for basic science courses, we found that our ARS strategy improved student motivation to participate and excel. This further illustrates the usefulness of this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…19 Clinical courses have introduced innovative pedagogies to motivate students and animate learning while most science courses remain strongly didactic, uninteresting, and of poor quality. 19 Although these challenges may exist for basic science courses, we found that our ARS strategy improved student motivation to participate and excel. This further illustrates the usefulness of this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…33 Professional actors are more likely to provide consistent performances, and clear instructions should be given to the actor to ensure patients are standardized. 34 Because of resource constraints, our framework proposes the use of non-staff SPs in OSCEs administered in the last two years of the curriculum, and the use of senior students as SPs for OSCEs administered in the first two years of the curriculum. Nonteaching faculty members and volunteers could also be recruited.…”
Section: Discussionmentioning
confidence: 99%
“…I really, really believe there are great pharmacies and great jobs out there and you just have to be patient and be picky and wait for the right thing to come your way. " (Waterloo) 6. Looking back on the process you took to get hired, what would you have done differently?…”
Section: Tension Between Professional Satisfaction and Practical Consmentioning
confidence: 98%
“…These tra ditional features of the pharmacy employment workplace have been a strong driver of stu dents' interest in the profession itself. 6 Over Anecdotally, pharmacy educators in Ontario have heard stories about a contracting and increasingly difficult job market for new graduates. We undertook this study to better understand this situation and its implications for students, employers and patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation